Pengaruh terpaan iklan televisi dan persepsi merek terhadap minat beli (Studi pada produk Blackberry di kalangan mahasiswa FE Universitas Islam Lamongan) - Luluk Nur Azizah (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2017)
The purpose of this study is to describe and analyze the positive and significant influence between the exposure of television advertising Blackberry products and brand perception of Blackberry products on the interest of buying Blackberry products on FE Students of Islamic University of Lamongan. The method used is survey method that takes a sample of 76 respondents FE Students of Islamic University of Lamongan. Data analysis techniques used are Product Moment Correlation analysis, multiple correlation, Linear Regression and Multiple Regression with SPSS V.13.0 for windows program. The results of research conducted, it can be seen that there is a positive and significant influence between the exposure of television advertising and brand perception of Blackberry products to the interest in buying Blackberry products. The results of the analysis show that this study supports the S-O-R theory in the Student FE population of Lamongan Islamic University.